Les Maltais à Djerba : l’évolution d’une communauté étrangère - Mallia, David (2004)
École Nationale d’Architecture et d’Urbanisme de Tunis
Keywords: Emigration – Malte – Djerba

Rue des Maltais: la vie de la colonie maltaise de Tunisie - Donato, Marc (Gandini, 2002)
Keywords: Emigration – Malte – Djerba

Murder in Jerba: Honour, Shame and Hospitality among Maltese in Ottoman Tunisia - Smith, Andrea (History and Anthropology, 2004)
Keywords: Emigration – Malte – Djerba